2017
DOI: 10.1186/s12889-017-4570-7
|View full text |Cite|
|
Sign up to set email alerts
|

Community-based initiatives improving critical health literacy: a systematic review and meta-synthesis of qualitative evidence

Abstract: BackgroundCritical health literacy enables older adults to make informed health decisions and take actions for the health and wellbeing of themselves and their community, within their own social and cultural context. A community-based approach has the potential to improve the critical health literacy of older adults and their communities. However, it is not clear how such initiatives consider critical health literacy. Therefore, this study explored how community-based initiatives address the critical health li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 42 publications
1
72
0
3
Order By: Relevance
“…However, from the standpoint of existing HL interventions targeting communities we found in the literature, the community is either understood as a setting (a place outside of the medical clinics) or as an aggregate of individuals [35,36]. Similarly to De Wit et al [42], we found that the focus of these studies was mainly on vulnerable populations such as migrant groups [43] and older people [35].…”
Section: Towards a New Concept For Community Health Literacymentioning
confidence: 72%
“…However, from the standpoint of existing HL interventions targeting communities we found in the literature, the community is either understood as a setting (a place outside of the medical clinics) or as an aggregate of individuals [35,36]. Similarly to De Wit et al [42], we found that the focus of these studies was mainly on vulnerable populations such as migrant groups [43] and older people [35].…”
Section: Towards a New Concept For Community Health Literacymentioning
confidence: 72%
“…skills and competencies, the outcomes of interest within current health literacy approaches, to capture the capabilities of value that allow individuals and communities to be health literate (see Robeyn's methodological process 39,49). Research that explores what individuals and communities consider important components of health literacy (5,33,47,57), and emphasises the role of social support, learning within social groups, culture, and social networks (e.g. 33,47) Participatory community approaches therefore are a good way to bring together the capabilities approach and health literacy fields as both have successfully utilised these methods.…”
Section: Adopting Capability Approach Methodsologiesmentioning
confidence: 99%
“…Research that explores what individuals and communities consider important components of health literacy (5,33,47,57), and emphasises the role of social support, learning within social groups, culture, and social networks (e.g. 33,47) Participatory community approaches therefore are a good way to bring together the capabilities approach and health literacy fields as both have successfully utilised these methods. Critical health literacy researchers have placed community participatory approaches at the centre of health literacy research and implementation.…”
Section: Adopting Capability Approach Methodsologiesmentioning
confidence: 99%
“…Several studies have researched this assumption, with interesting results. For example, de Wit and colleagues [60] conducted a metaanalysis showing that social support and co-learning in communities were essential for critical health literacy based on qualitative evidence.…”
Section: Discussionmentioning
confidence: 99%